Assessing personal talent determinants in young racquet sport players: a systematic review - Faber, I. R.; Bustin, P. M. J.; Oosterveld, F. G. J.; Elferink-Gemser, M. T.; Nijhuis-van der Sanden, M. W. G. (Journal of Sports Sciences, 2016)
Since junior performances have little predictive value for future success, other solutions are sought to assess a young player`s potential. The objectives of this systematic review are (1) to provide an overview of instruments measuring personal talent determinants of young players in racquet sports, and (2) to evaluate these instruments regarding their validity for talent development. Electronic searches were conducted in PubMed, PsychINFO, Web of Knowledge, ScienceDirect and SPORTDiscus (1990 to 31 March 2014). Search terms represented tennis, table tennis, badminton and squash, the concept of talent, methods of testing and children. Thirty articles with information regarding over 100 instruments were included. Validity evaluation showed that instruments focusing on intellectual and perceptual abilities, and coordinative skills discriminate elite from non-elite players and/or are related to current performance, but their predictive validity is not confirmed. There is moderate evidence that the assessments of mental and goal management skills predict future performance. Data on instruments measuring physical characteristics prohibit a conclusion due to conflicting findings. This systematic review yielded an ambiguous end point. The lack of longitudinal studies precludes verification of the instrument`s capacity to forecast future performance. Future research should focus on instruments assessing multidimensional talent determinants and their predictive value in longitudinal designs.